Lawrence Abu Hamdan : Dirty Evidence - Abu Hamdan, Lawrence; Andrea Lissoni; Eyal Weizman; Fabian Schoneich; Lawrence Abu Hamdan; Natasha Ginwala; Ramona Naddaff; Ruba Katrib; Theodor Ringborg; Yasmine Seale (Stockholm; Bonniers Konsthall; Lenz Press, 2021)
On the occasion of Lawrence Abu Hamdan's exhibition at Bonniers Konsthall in Stockholm in 2021, a group of authors have been invited to engage with individual works and their underlying concepts. Abu Hamdan recognizes the space for art as a site where attention can be drawn to real socio-political conditions in order to challenge the structures behind them. The artist can therefore push at the boundaries of what constitutes testimony. The title "Dirty Evidence" comes from Abu Hamdan's definition of evidence in which a truth value is derived from its very inadmissibility before the law. It is precisely the evidence's figurative dirt and dirtiness that works toward the production of truth.
English
Keywords: N4390-5098 Exhibitions